An Ultrasensitive and Ultraselective Hydrogen Sensor Based on Defect‐Dominated Electron Scattering in Pt Nanowire Arrays. Issue 1 (19th November 2018) - Cao, Fan; Zhao, Pengfei; Wang, Zhao; Zhang, Xianghui; Zheng, He; Wang, Jianbo; Zhou, Di; Hu, Yongming; Gu, Haoshuang
Abstract: The detection of hydrogen gas has attracted extensive attention due to its wide applications. Here, ultrathin Pt nanowires (3.5 nm) with abundant defects are fabricated by focused ion beam (FIB) for hydrogen detection. Different from the surface‐dominated scattering in previous reports where the resistance of Pt decreases after hydrogenation, the Pt hydrogen sensor prepared by FIB is based on defect‐dominated electron scattering owing to the abundant defects, i.e., the resistance is dominated by defect scattering, while H atoms will diffuse along the defects and thus enhance the electron scattering and resistance. Thanks to the small volume of H atoms (easy to diffuse along defects), the sensor is very sensitive and selective to hydrogen and exhibits fast response–recovery properties. Moreover, the sensitivity can be improved after the response–recovery loops, which may be ascribed to the generation of extra defects (further accelerating H atom diffusion). After response in pure H2 and recovery in air, the sensor has an ultralow limit of detection (for H2 in air) of 10 ppb. The results present a hydrogen sensor with superior sensitivity and selectivity, which would not only facilitate the development of metal hydrogen sensors, but also provide a feasible strategy for hydrogen detection. Abstract : A hydrogen sensor is fabricated based on Pt nanowire arrays prepared by focused ion beam. Different from the surface‐dominated sensing mechanism in previous works, the sensor shows a defect‐dominated electron scattering behavior in Pt nanowires, exhibiting superior sensitivity and selectivity due to the fast and exclusive diffusion of H atoms along the defects.